'We are at this campus, there is nothing in this campus …': Socio-spatial analysis of a university campus. Issue 1 (2nd January 2017) - Ağlargöz, Ozan
Abstract : This article provides a socio-spatial analysis of a higher education institution operating within a multi-campus system at a location other than the flagship campus. Based on this case study of a technical school, the meanings attached to the university campus are analyzed through semi-structured interviews and official documents. The study reveals how strong resource dependency in terms of the funds necessary for conducting core functions (i.e. research) silences tensions and apathy between the university and the affiliated schools. The socio-spatial analysis based on Lefebvre's triad reveals hidden concerns such as loneliness, isolation, and inattentiveness. Overall, the paper underlines the importance of viewing the campus as a social space, and presents potential outcomes not only for policy makers but also for multi-campus system research endeavors.